The Urgency of Formulating Clear Accessibility Norms for the Effectiveness of Fulfilling Disability Rights - Monalisa Anggraini Habeahan; Dina Lolita Aulia; Arum Prasetya Rini; Faza Rahma Anggraini; Sjazilda Sjamsu (Universitas Negeri Surabaya, 2025)
People with disabilities in Indonesia still face various obstacles in fulfilling their rights, especially in relation to accessibility, discrimination, and negative stigma. This study examines the implementation of Law No. 8 Year 2016 regarding persons with disabilities, which is not fully effective in ensuring physical access, transportation, education, and employment opportunities for persons with disabilities. This study uses a normative legal method with a qualitative approach to analyze the unclear legal definition of “accessibility” and its impact on the performance of the rights of persons with disabilities. The results of the study show that there are national and local regulations, such as those in Denpasar City and BOA Lemory Regency, which still limit discrimination and access to public institutions. Cultural factors and local values also influence local governments' acceptance of the rights of persons with disabilities. This article provides recommendations for the government to create an integrated environment and design more detailed guidelines regarding accessibility to support the independence of persons with disabilities.